Study on Motorcycle Crash Cost in Bandung City - Safety Husna Pangestika; Aine Kusumawati; Ade Sjafruddin (Jurnal Teknik Sipil, 2021)
Crash cost is an important component for conducting economic analysis in selecting countermeasures for crash locations. It is used to convert the benefit of crash or fatality reduction into monetary terms. Many research on crash cost have been carried out in Indonesia. Most of the research utilized gross output/human capital approach. However, this approach has been widely criticized for not being able to describe the quality of life of crash casualties and the costs of pain, grief and suffering (i.e. human cost). The concept of Value of Statistical Life  (VoSL) has been introduced by InDeV (2016) to calculate the human cost, which is assessed by using willingness to pay approach. To obtain a more reliable estimation of crash cost for Indonesia, it is necessary to conduct a study on crash cost involving motorcycles which incorporates the estimation of human cost. The VoSL is obtained by interviewing motorcycle users for willingness to pay with safety equipment. Based on the analysis, it is obtained that the value of statistical life (VoSL) for fatality in a road crash was estimated to be Rp.2.3 billion. The unit cost of fatal injury is Rp.3.08 billion, serious injury is Rp.333 million and slight injury is Rp.24.9 million. The unit cost of fatal crash on arterial roads is Rp.3.23 billion, serious crash is Rp.451 million and the slight crash is Rp.114 million. The unit cost of fatal crash on collector roads is Rp.3.16 billion, serious crashes is Rp.381 million and minor crash is Rp.69.4 million. The unit cost of fatal crash on local roads is Rp.3.09 billion, serious crash is Rp.338 million, and minor crash is Rp.29.8 million. Keywords: Motorcycle crash cost, gross output approach, human capital approach, willingness to pay approach